Early Language Experience in a Tseltal Mayan Village. Issue 5 (31st December 2019) - Casillas, Marisa; Brown, Penelope; Levinson, Stephen C.
Abstract : Daylong at‐home audio recordings from 10 Tseltal Mayan children (0;2–3;0; Southern Mexico) were analyzed for how often children engaged in verbal interaction with others and whether their speech environment changed with age, time of day, household size, and number of speakers present. Children were infrequently directly spoken to, with most directed speech coming from adults, and no increase with age. Most directed speech came in the mornings, and interactional peaks contained nearly four times the baseline rate of directed speech. Coarse indicators of children's language development (babbling, first words, first word combinations) suggest that Tseltal children manage to extract the linguistic information they need despite minimal directed speech. Multiple proposals for how they might do so are discussed.